Nutritional Characteristics of Selected Insects in Uganda for Use as Alternative Protein Sources in Food and Feed. Issue 6 (18th December 2019) - Bbosa, Tom; Tamale Ndagire, Catherine; Muzira Mukisa, Ivan; Fiaboe, Komi K M; Nakimbugwe, Dorothy
Abstract: Insects are potential ingredients for animal feed and human food. Their suitability may be influenced by species and nutritional value. This study was aimed at determining the nutritional profile of four insects: Dipterans; black soldier fly ( Hermetia illucens Linnaeus) family stratiomyidae and blue calliphora flies ( Calliphora vomitoria Linnaeus) family Calliphoridae; and orthopterans; crickets ( Acheta domesticus Linnaeus) family Gryllidae and grasshoppers ( Ruspolia nitidula Linnaeus) family Tettigoniidae to establish their potential as alternative protein sources for animals (fish and poultry) and humans. Gross energy, crude protein, crude fat, crude fiber, carbohydrates, and total ash were in the ranges of 2028.11–2551.61 kJ/100 g, 44.31–64.90, 0.61–46.29, 5.075–16.61, 3.43–12.27, and 3.23–8.74 g/100 g, respectively. Hermetia illucens had the highest energy and ash content; C. vomitoria were highest in protein and fiber content, R. nitidula were highest in fat, whereas A. domesticus had the highest carbohydrate content. All insects had essential amino acids required for poultry, fish, and human nutrition. The arginine to lysine ratios of H. illucens, C. vomitoria, A. domesticus, and R. nitidula were 1.45, 1.06, 1.06, and 1.45, respectively. The fatty acids comprised of polyunsaturated fatty acids (PUFAs) and saturated fatty acids (SFAs). Palmitic acid (23.6–38.8 g/100 g of total fat) was the most abundant SFA, exception R. nitidula with 14 g/100 g stearic acid. Linoleic acid (190–1, 723 mg/100 g) and linolenic acid (650–1, 903 mg/100 g) were the most abundant PUFAs. Only C. vomitoria had docosahexaenoic acid. The study indicates that the insects studied are rich in crude protein and other nutrients and can potentially be used for human and animal (fish and poultry) feeding.